Fatigue behavior of Ti-6Al-4V alloy modified by plasma immersion ion implantation: Temperature effect. - Velloso, Verônica [UNESP]; Nozaki, Leonardo [UNESP]; Tapia, Diego; Cioffi, Maria Odila [UNESP]; Oliveira, Rogério; Barboza, Miguel; Voorwald, Herman [UNESP] (EDP Sciences, 2018)
This research studied Ti-6Al-4V alloy behavior with two (2) different microstructure subjected to nitrogen addition by PIII treatment, with and without sample heating, under cyclic load. PIII conditions, at 390 °C, were DC voltage of 9.5 kV, frequency of 1.5 kHz and pulse of 40 μs. PIII conditions, with sample heating at 800 °C, were 7 kV, 0.4 kHz and 30 μs. Axial fatigue tests were performed on untreated and treated samples for resistance to fatigue comparison. The untreated Ti-6Al-4V had an annealed microstructure, PIII treatment at 390 °C resulted in a microstructure that has no nitride layer or diffusion zone. In the PIII treatment at 800 °C, the microstructure presented nitride layer and diffusion zone. Resistance to fatigue decreased with PIII treatments in both temperatures. At 390 °C, the treatment created deformation regions and cracks on surface due to nitrogen implantation that formed solid solution with titanium and imposed lattice strains on the crystal lattice. At 800 °C, bulk ductility decrease, increasing of αTi proportion in microstructure due to α case formation and the presence of a ceramic layer dropped fatigue resistance of Ti-6A-4V alloy.